Impact of dehydroepiandrosterone sulfate and free androgen index on pregnancy and neonatal outcomes in PCOS patients - Zhao, Wen; Li, Zeting; Cai, Bing; Zhou, Canquan; Mai, Qingyun (Reproductive biology and endocrinology, 2024)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder associated with infertility and pregnancy complications. The pathogenesis of PCOS and its impact on reproductive function may be influenced by the source of androgens, including testosterone, free androgen, dehydroepiandrosterone sulfate (DHEAS). However, the differential effects of these androgen on pregnancy and neonatal outcomes and the cut-off value of East Asian population with PCOS remain unclear. A retrospective cohort study was conducted at the Reproductive Medicine Center of the First Affiliated Hospital of Sun Yat-sen University from January 2015 to November 2022, involving 636 cycles of in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). Subgroup analyses were performed using cut-off values of 6.4 for free androgen index (FAI), 9.5 µmol/L for DHEAS. Pregnancy and neonatal outcomes were compared between groups. Restricted cubic spline (RCS) was used to identify significant cut-off values affecting pregnancy. Higher FAI levels (> 6.4) were associated with decrease in clinical pregnancy rate (PR) (50.61% vs. 41.66%, p = 0.024), live birth rate (LBR) (42.42% vs. 32.35%, p = 0.011). When DHEAS levels exceeded 9.5 µmol/L, there was a significant decrease in clinical PR (51.27% vs. 42.73%, P = 0.039), LBR (42.73% vs. 32.73%, P = 0.012). Negative correlations were also observed between DHEAS levels and cumulative pregnancy rate (70.57% vs 56.62% p = 0.002) and cumulative live birth rate (CLBR) (59.35% vs 43.37%, p = 0.0007). Both FAI and DHEAS elevated is associated with the lowest clinical pregnancy rate (37.84%). Conversely, when solely FAI is elevated, the pregnancy rate increases to 52.38%, while an elevation in DHEAS alone is associated with a pregnancy rate of, both of which are lower than when neither FAI nor DHEAS are elevated (60.68%). The live birth rates exhibit a similar trend (30.00% vs 40.00% vs 41.83% vs 44.48%). RCS revealed a significant decrease in CPR and CLBR when DHEA levels exceeded 7.69 umol/L, while the cut-off value of FAI was 6.36 for CPR and CLBR. In conclusion, PCOS patients with biochemical hyperandrogenism show unsatisfactory clinical PR and CLBR when undergoing assisted reproductive technology (ART). This may be attributed to the influence of both adrenal-derived DHEAS and ovarian-derived FAI on the unfavorable pregnancy outcomes.